Differences in unilateral chest press muscle activation and kinematics on a stable versus unstable surface while holding one versus two dumbbells - Patterson,Jeffrey M.; Vigotsky,Andrew D.; Oppenheimer,Nicole E.; Feser,Erin H. (PeerJ, 2015)
Training the bench press exercise on a traditional flat bench does not induce a level of instability as seen in sport movements and activities of daily living. Twenty participants were recruited to test two forms of instability: using one dumbbell rather than two and lifting on the COR bench compared to a flat bench. Electromyography (EMG) amplitudes of the pectoralis major, middle trapezius, external oblique, and internal oblique were recorded and compared. Differences in range of motion (ROM) were evaluated by measuring an angular representation of the shoulder complex. Four separate conditions of unilateral bench press were tested while lifting on a: flat bench with one dumbbell, flat bench with two dumbbells, COR Bench with one dumbbell, and COR Bench with two dumbbells. The results imply that there are no differences in EMG amplitude or ROM between the COR bench and traditional bench. However, greater ROM was found to be utilized in the single dumbbell condition, both in the COR bench and the flat bench.
Keywords: COR bench; Bench press; Dumbbell press; Dumbbell bench; Electromyography; EMG; Range of motion; ROM; Stability; Cocontraction